Grantmaking and civil society organisations - Chetty, Chimene Paranjothie (My University, 2014)
The 1990s has seen considerable interest generated in the development of civil society in the different regions of the world. Non-governmental organisations (NGOs), community based organisations (CBOs) and other civil society associations and formations are seen as important contributors to constructive social change. It has been no different in South Africa Most South African civil society organisations (CSOs) rely entirely on funding as their means of income. This study examines the relationship between the funder and CSOs and possible means of making the relationship more constructive and responsive to the needs of CSOs. In particular the study examines the grantmaking components of the funding process and how these components can be refined to meet the needs of CSOs. The study found that there were several ways of refining the grantmaking process to be more value-adding to CSOs.
A research report submitted to the Faculty of Management, University of Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Public and Development Management). February, 2000